CAPITALISMO COMO RELIGIÃO: Uma crítica a seus fundamentos mítico-teológicos. - Coelho, Allan da Silva (2014)
Would be possible to understand capitalism as religion? In categorical landmarks of modernity, based on rationalization and secularization, relate economics and religion is a nonsense. The capitalism is a secular system economic, so unrelated with religion. However, if critique of capitalism as religion not reduced to a simple metaphor, is necessary to find alternative concepts that capture the theoretical strength of this articulation. What kind of analytical framework reveals the limits of instrumental reason in make explicit the religious functioning of capitalism? The critical depth of capitalism as religion comes precisely from the intriguing junction between rational analyses of the structural functioning of capitalism (fetish) with the subjective dimension that drives as motivation (spirit). Even being a rational and non-religious system, which submits the human life to domestic laws destitute of any human sense, the capitalism develops not intentionally in the human interaction an operating structure based on sacrificial mythical-religious. The Human relationships are mediated by merchandise where the consumption takes on a central aspect in the meaning of the life and the symbolic reproduction of society. In the production and distribution of goods, the violence process, which explores, excludes and kills, is the same that generates fascination and adhesion. The visible expression of this spirit is no longer in traditional religious institutions, but in capitalism itself. Benjamin asserts that capitalism replaces the religion. Is a critique of a system of blaming the victims and the capitalists themselves, in that it never accumulate infinite and fully. Is a complaint of mythical elements that generate religious legitimacy to the fascination that hidden the barbarism. The theologians of DEI School also articulate his theory with critical purpose, in a theological approach that search to discern and criticize the idolatry in the world today. Looking for to understand the producing mechanisms of death placing the blame the victims as necessary sacrifice in the name of the hope of redemption. The theological discernment of capital idolatry supposes a kind of theological reason of non-confessional character, which surpassing the limits of modern epistemology, explains the contradiction of the presuppositions of modern western civilization. Reveals the role of the mythical-theological thinking in the hiding of the sacrificial character and seductive of the capitalism spirit. At the same time, emphasizes the necessary overcoming of positivistic interpretation of religion by criticizing reductionism of modern epistemology in the identification of instrumental reason with the human rationality. Renews the analytical tools from the spiritual setting of Capitalism and sees the loopholes of its overcoming.